Gambaran Strategi Pembelajaran Partisipatif pada Kegiatan Pembelajaran Bahasa Indonesia dalam Program Paket B di PKBM Tanjung Sari Kota Sawahlunto - Aldilla Hidayati; Setiawati Setiawati; Vevi Sunarti (Universitas Negeri Padang, 2018)
This research is motivated by the activity of learning package B Indonesian language subjects get high score. This is thought to have something to do with the participatory learning strategy used by tutors. This study aims to describe participatory learning strategies by tutors in B package program of Indonesian subjects which include: (1) planning of learning activities, (2) implementation of learning activities, (3) evaluation of learning activities. This type of research is descriptive quantitative. This study did not conduct sampling, therefore the entire population was made a respondent. Data collection techniques used are questionnaires, while data collection tools use questionnaires. Data analysis techniques using the formula percentage. Suggestions for this research, so that participative learning strategies can be improved again by tutors in learning Indonesian and other learning.